Flavonol glycosides from the fruits of Evodia rutaecarpa. Issue 9 (2nd September 2018) - Liu, Shan-Shan; Dai, Yun-Tao; Sui, Feng; Chen, Liang-Mian; Yan, Li-Hua; Zhang, Qi-Wei; Wang, Zhi-Min
Abstract: Two new flavonol glycosides, limocitrin 3-O- β -D-xylopyranosyl(1→2)- β -D-glucopyranoside (1 ) and limocitrin 3-O[2-O- β -D-xylopyranosyl-6-O- α -L-rhamnopyranosyl]- β -D-glucopyranoside (2 ), together with eight known analogs (3–10 ), were isolated from the fruits of Evodia rutaecarpa . Their structures were elucidated on the basis of spectroscopic analyses and chemical evidences. Meanwhile, Nrf2 inducing abilities of seven isolated compounds were evaluated, and compounds1, 2, 6, 7, and8 exhibited moderate effect on Nrf2. Abstract :